2022
DOI: 10.3390/f13010130
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Economic Contribution of Forest Use to Rural Livelihoods in the Rubi-Tele Hunting Domain, DR Congo

Abstract: Forest utilization makes a significant economic contribution to the livelihoods of rural households, especially those living in developing countries. This study was conducted to determine the absolute and relative forest income and measure the distributional impact of forest income on economic inequalities among rural households in the Rubi-Tele Hunting Domain (RTHD), Democratic Republic of the Congo (DR Congo). Household socioeconomic data and other qualitative informations were collected using structured hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 83 publications
(172 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the tropical rainforests of Congo are a key factor in producing oxygen and regulating global temperature through the absorption of solar radiation by forest massifs. Moreover, forest resources offer critical and principal support to the welfare of rural livelihoods and the socioeconomic wellbeing of the local population [87], which includes forest-related practices such as forest clearing. As a result, land use and shifting agriculture have become the major causes of the hydrological flow regime, environmental changes from the regional to global scale [88], as well as deforestation, along with the increased population density and associated urban growth [89].…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, the tropical rainforests of Congo are a key factor in producing oxygen and regulating global temperature through the absorption of solar radiation by forest massifs. Moreover, forest resources offer critical and principal support to the welfare of rural livelihoods and the socioeconomic wellbeing of the local population [87], which includes forest-related practices such as forest clearing. As a result, land use and shifting agriculture have become the major causes of the hydrological flow regime, environmental changes from the regional to global scale [88], as well as deforestation, along with the increased population density and associated urban growth [89].…”
Section: Study Areamentioning
confidence: 99%
“…There are many ways that forest ecosystem services support rural livelihoods (Ahammad et al, 2019). Households in the low-income group depended more on forest resources (Mendako et al, 2022) Communities living near forests rely heavily on forest resources (Munawaroh et al, 2011). This is because the forest provides basic needs like food and animal feed (Haryani & Rijanta, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies found that the percentage of rural households relying on forest income globally varies between 28% and 33% [4], [5]. Environmental revenue accounts for 28% of total household income, with 77% coming from natural forests [4].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental revenue accounts for 28% of total household income, with 77% coming from natural forests [4]. Another study found that the proportion of forest income to total household income ranged from 32% to 33%, with wood fuel being the largest source of income [5].…”
Section: Introductionmentioning
confidence: 99%